Cytotoxic effects of ergone, a compound isolated from Fulviformes fastuosus - Fernando, Dilusha; Adhikari, Achyut; Nanayakkara, C.M.; de Silva, E Dilip; Wijesundera, Ravi; Soysa, Preethi (BMC Complementary and Alternative Medicine, 2016)
Background: Mushrooms inspired the cuisines of many cultures and conventional medicaments for cancer. However, a substantial number of mushroom species are yet unexplored, possessing an unknown chemical, biological and pharmacological profiles. Fulviformes fastuosus is a terrestrial mushroom, which is commonly found in Sri Lankan woodlands. The current study was aimed at isolation and characterization of a potent cytotoxic compound from F. fastuosus and investigating the apoptotic effect induced by the active principle against cancer and normal cell lines. Methods: Bioactivity guided isolation of active principles from the methanol extract of F. fastuosus was performed by a rapid extraction and isolation method using different chromatographic techniques. Potential cytotoxic compound was identified using one and two dimensional nuclear magnetic resonance spectroscopy and mass spectrometry. Isolated compound was screened for in vitro cytotoxicity against Hepatocellular carcinoma (HepG-2), Muscle rhabdomyosarcoma (RD) and Rat Wistar liver normal (CC-1) cell lines using 3 4, 5-(dimethylthiazol-2-yl) 2-5- diphenyl tetrazolium bromide (MTT) cell viability assay. Apoptotic features of cells were observed via microscopic examination and ethidium bromide/acridine orange fluorescent staining. Results: The interpretation of spectral data resulted in the identification of the chemical structure as ergosta-4,6,8 (14),22-tetraen-3-one (ergone). Ergone exhibited promising cytotoxic properties against RD cells with less cytotoxicity effect on CC-1 cells. In addition, ergone also possesses a strong cytotoxic effect against HepG-2 cells showing low toxic level for CC-1 cells. Apoptotic features of treated cells were detected via morphological characterization and ethidium bromide/acridine orange staining. Conclusion: The present study elaborates the isolation of a potent cytotoxic compound; ergone, from F. fastuosus via a rapid and efficient isolation method. Importantly, ergone has exhibited greater cytotoxic activity against RD cells with high selectivity index compared to cytotoxicity against HepG-2 cells. Ergone can be used in the development of therapeutic strategies for curbing rhabdomyosarcoma.
Keywords: Mushrooms, Fulviformes fastuosus, Isolation method, Ergone, Cytotoxic activity, Rhabdomyosarcoma, Hepatocellular carcinoma